Pengaruh Pemanasan Bahan Bakar dan Penambahan Biodiesel Pada Solar terhadap Konsumsi Bahan Bakar Mesin Diesel Mitsubishi L300 - Arga Hartantyadhi Pratama; Danar Susilo Wijayanto; Ngatou Rohman (Jurnal Mekanika dan Sistem Termal, 2016)
The purpose of this research is to investigate effect of biodiesel adding into diesel fuel and effect of fuel heating through spiral-fin pipes in the radiator upper tank towards Mitsubishi L300 Diesel Engine fuel consumption. This research was a descriptive quantitative with experiments methods. Sample on this research was a Mitsubishi 4 cylinder type L300 Diesel Engine. Data was getting from measuring Mitsubishi L300 Diesel Engine fuel consumption with the 0 %, 5%, 10%, 15%, 20%, 25% and 30% of biodiesel mix variations, it was included with without heating variations; non-fin pipes heating; and finned pipes heating with inter fin variation was 2 spiral thread, 4 spiral thread, 6 spiral thread, and perpendicular-fin. Result of this research shows as: (1) It has an effect of biodiesel adding into diesel fuel on the Mitsubishi L300 Diesel Engine.; (2) It has an effect of fuel heating using spiral-fin pipes in the upper tank radiator on reducing Mitsubishi L300 Diesel Engine fuel consumption.; (3) It has an effect of biodiesel adding and fuel heating on reducing fule consumption in the Mitsubishi L300 Diesel Engine. The biggest reducing of fuel consumption happens on 20% biodiesel : 80% fuel diesel fuel level and fuel heating using pipes with 6 spiral thread inter-fin variation that is as much as 9.331 ml/minute every cycle. Consumption reducing is 1.320 ml/minute ar as much as 12.393% from standart consumption.